Korelasi Religiusitas dengan Psychological Well-Being pada Lansia: Correlation of Religiosity with Psychological Well-Being in the Elderly - Laili, Nurul; Hayati, Farida (Jurnal Abdi Keperawatan dan Kedokteran, 2026)
The aging process brings physical and psychological changes that can impact on the mental health of the elderly. Anxiety is often triggered by the death of a loved one, which can lead to feelings of loneliness. Elderly individuals with high levels of religiosity exhibit better attitudes, are satisfied with their lives, and experience less loneliness. The purpose of this study was to determine the relationship between religiosity and psychological well-being among elderly individuals at the Tanjung Elderly Community Health Post (Posyandu Lansia) in Bendo Village. The study design employed a correlational cross-sectional approach. The sampling technique used purposive sampling, selecting 60 respondents from a population of 75. The research instruments used a religiosity questionnaire and the Ryff's Psychological Well-Being Scale. Statistical tests used Spearman's rho with a significance level of 0.05. The results showed that the majority (76.7%) of respondents had high levels of religiosity and the majority (65%) had high levels of psychological well-being. The analysis yielded a p-value of 0.000 ≤ 0.05 and a coefficient between variables of 0.669, indicating a high correlation between religiosity and psychological well-being in the elderly at the Tanjung Elderly Posyandu in Bendo Village. The higher the elderly's religiosity, the higher their psychological well-being. The concept of surrender and emotional and psychological calm that results from a positive interaction with God impacts both physical and mental health. A well-conditioned environment with spiritual activities can support seniors in living well.